(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The establishment of a Unified Client Database (CDB) system and the associated ePRO program has dramatically improved the efficiency of benefits administration for organizations. This client-centric approach provided the Technical Lead from the Engineering Group with the ability to create an end-to-end data framework using normalized, metadata-driven design that supports intricate multi-client benefit structures, secured ETL/API connections to ensure seamless integration of enrolment, human resource and claims systems with robust data governance through automated data validation, audit logging and version control. The platform was developed for a cloud-based environment with the use of Redshift to support analytics and AWS S3 to serve as the archive for the repository of data, supported with telemetry dashboards to enable real-time visibility into the health of synchronization and ingestion latency. Implementing the platform has resulted in near real-time downstream integration with the subsequent increase in the timeliness and accuracy of data which has reduced the number of manual reconciliation errors by greater than 25% while improving compliance controls. In alignment with the trend towards the utilization of data-based automation within enterprise EPM Modernization, the CDB platform enables organizations to onboard clients quicker, achieve greater operational transparency and provide a scalable foundation for future cloud services. The next phase of enhancements will seek to evolve the CDB platform into a fully automated cloud-based ecosystem, including developments related to AI-based anomaly detection; enhanced capabilities to expand on serverless microservices; and advanced analytics using Redshift to provide predictive insight regarding benefit-related usage.